2023
DOI: 10.56182/djog.v2i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal laser therapy for urogenital symptoms in postmenopausal women and breast cancer survivors

Sine Jacobsen,
Finn Friis Lauszus,
Cathrine Krogh Jeppesen
et al.

Abstract: Introduction: Genitourinary syndrome of menopause (GSM) is common after natural menopause as well as in women with induced menopause due to endocrine therapy and/or oophorectomy following breast cancer. Vaginal laser therapy is a nonhormonal treatment option that appears to alleviate GSM symptoms in natural menopause; however, women with induced menopause may respond differently. The aim of this study was thus to evaluate the efficacy and safety of laser treatment on GSM in postmenopausal women and breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A Danish study undertaken in women following both natural menopause and induced menopause, as a result of endocrine therapy or oophorectomy for breast cancer, found that all women experienced an improvement in symptoms, relating to sexual and urinary function. 1 Another study undertaken in women with a history of breast cancer found no serious adverse effects. 2…”
Section: Discussionmentioning
confidence: 98%
“…A Danish study undertaken in women following both natural menopause and induced menopause, as a result of endocrine therapy or oophorectomy for breast cancer, found that all women experienced an improvement in symptoms, relating to sexual and urinary function. 1 Another study undertaken in women with a history of breast cancer found no serious adverse effects. 2…”
Section: Discussionmentioning
confidence: 98%